Risk preferences, intra-household dynamics and spatial effects on chemical inputs use: Case of small-scale citrus farmers in Indonesia. (November 2022) - Hasibuan, Abdul Muis; Gregg, Daniel; Stringer, Randy
Abstract: The use of chemical fertilisers and pesticides is rapidly increasing in developing countries. If used appropriately, these inputs are key approaches to enhancing farm productivity including mitigating potential damage caused by climate change. Yet there is also an increasingly concerning trade-off between chemical input applications and environmental externalities in communities of smallholder farmers. Furthermore, fertilisers and pesticides account for a high proportion of farm input expenses, especially for high-value horticultural crops, impacting on the risks facing farmers and potentially limiting other household needs for cash-constrained households. Given the potential impacts of chemical input purchases on household expenditures and the joint roles of male and female spouses in farming activities in Indonesia, these input purchase decisions may involve complex intra-household dynamics between spouses. Moreover, small-scale farmers in rural areas often refer to their neighbour farmers in managing their farm. In this paper, we consider the independent and joint roles that risk, intra-household dynamics, and extra-household (spatial) dynamics play in decisions regarding household expenditure on chemical fertilisers and pesticides. Using spatial regression models, we find that these factors are all associated with household expenditures on chemical inputs. The results also indicate the importance of social networking in the decision of chemical pesticides and fertilisers usage. Highlights: Farm sustainability and productivity is more complicated with climate change issues. Intensification is important to increase farm productivity and food security. Chemical inputs use among citrus farm households exhibits the spatial correlation. Intrahousehold dynamics and risk preferences are associated with insecticides use.